Pharmacogenomics in clinical therapeutics - Langman, Loralie J.; Dasgupta, Amitava, 1958-; Wiley InterScience (Online service) (Hoboken : John Wiley & Sons, 2012)
Pharmacogenomics is the process of analyzing patients' genes to predict the onset of adverse reactions or forecast the effectiveness of therapeutic drugs. This useful text is written to discuss both the theory and the clinical application of the principles of pharmacogenomics. Current research has clearly established that a range of treatments may be greatly improved through genetic profiling of individual patients before certain therapies begin. Aimed at clinicians, pharmacologists, and clinical laboratory professionals this book discusses the important role of laboratory tests in the practice of personalized medicine. An important new book, Pharmacogenomics in Clinical Therapeutics serves as a guide to the basic principles of pharmacogenomics in a range of common therapeutic areas and as the basis of the personalized medicine of the future.
Front Matter -- Pharmacogenomics Principles: Introduction to Personalized Medicine / Parvaz Madadi, Gideon Koren -- Traditional Therapeutic Drug Monitoring and Pharmacogenomics: Are They Complementary? / Christine L H Snozek, Loralie J Langman, Amitava Dasgupta -- Pharmacogenomics Aspect of Warfarin Therapy / Matthew D Krasowski -- Pharmacogenetics and Cancer Chemotherapy / Christine L H Snozek -- Pharmacogenomic Considerations in Anesthesia and Pain Management / Christine M Formea, Wayne T Nicholson -- Pharmacogenomics of Immunosuppressants / Nicolas Picard, Pierre Marquet -- Pharmacogenomics of Cardiovascular Drugs / Linnea M Baudhuin -- Pharmacogenomic Aspects of Antiretroviral Therapy / Natella Y Rakhmanina, John N van den Anker -- Pharmacogenetics of Psychoactive Drugs / Jorge L Sepulveda -- Pharmacogenomic Aspects of Adverse Drug-Drug Interactions / Loralie J Langman, Christine L H Snozek -- Microarray Technology and Other Methods in Pharmacogenomics Testing / Jorge L Sepulveda -- Pharmacogenetic Testing in the Clinical Laboratory Environment / Mark P Borgman, Mark W Linder -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Pharmacogenetics; Chemotherapy; Chemotherapy; Pharmacogenetics; Electronic books